Sometimes I Don't Feel Like Praying - Jones, Mike; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2008)
This is a book primarily about grace. In it you will also find out how God's grace can enable you with spiritual power to exchange your old life for a new one.
Keywords: Adult Nonfiction